Efeito da suplementação parenteral de minerais e vitaminas sobre o desempenho de vacas nelore - Costa, Claudio (2006)
The productive and reproductive performances were evaluated on Nelore cows supplemented with minerals and vitamins parenteral via. One hundred and twenty cows were randomly allotted into five treatment groups. Treatment one was the control group which did not receive any medication; to group two 479 mg of copper + 3 mg of cobalt was applied; group three received 3.45 g of phosphorus + 750000 IU of D2 vitamin + 0.42 g calcium; to group four 5000 IU of E vitamin + 1200000 of IU D2 vitamin + 0.075 g of selenium + 7 g phosphorus were administered and group five was an association of treatment groups two and three. The animals received a dose of these injectable minerals and vitamins thirty days prior to the breeding season and another thirty days after the first application. The reproductive evaluation and weighing were carried out monthly from October 15, 2004 to March 15, 2005 in the town of Douradoquara, Minas Gerais State. The weight gain and the score of body condition were analyzed through Kruskal Wallis test, and the ovarian condition and pregnancy rate through the Chi-square test. It was observed that the parenteral supplementation of minerals and vitamins did not influence the weight gain, the score body condition, the ovarian condition or the pregnancy rate of Nelore cows grazing native pasture.